Relationship between Premature Rupture of Membranes to Neonatal Sepsis: A Literature Review - Fariz Augusta (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Infection is still one of the highest cause of neonatal death in Indonesia. 30% of neonatal deaths are caused by infection (Kosen, 2005), with numbers ranging from 8,76% to 30,29% with fatality rates of up to 49,9% (Victor,1997). Several journals has discussed the relationship between premature rupture of membranes and neonatal sepsis. The author will review said literatures and conclude them.Aims of the Study: This review aims to analyze how premature rupture of membranes may cause neonatal sepsis and does the former increases risk of the latter.Methods of Study: Data will be appraised from associated literatures and synthesizing the results. Reviewed literatures are taken from Pubmed, NCBI PMC, and Google Scholar. Literature criteria are observational study with control, comparative study, and analytical descriptive study.Results: 13 literatures that discussed the relationship between premature rupture of membranes with neonatal sepsis were reviewed. While neonatal sepsis still occurs in women without premature rupture of membranes, women with premature rupture of membranes has marked a higher incidence of neonatal sepsis. The risks of neonatal sepsis are multifactorial, such as (1) low birth weight, (2) preterm premature rupture of membranes, (3) premature rupture of membranes with longer durations, and (4) healthcare quality.Conclusion: Premature rupture of membranes is shown to increase risk of neonatal sepsis occuring.